One-Third of Patients With Type 2 Diabetes Mellitus Do Not Have Coronary Artery Calcification - ML, Tofterup; H, Beck-Nielsen; O, Gerke; K, Egstrup; NPR, Sand; H, Munkholm; H, Mickley; ACP, Diederichsen (Journal of Preventive Medicine And Care, 2015)
Objective Measuring coronary artery calcification (CAC) enables to optimize cardiovascular risk-stratification also in patients with type 2 diabetes mellitus (T2D), however the prevalence of CAC in randomly selected patients with T2D is uncertain. For this purpose we set out to examine and compare the occurrence of CAC in unselected T2D patients. Design A randomly selected cohort of 1825 individuals, men and women, either 50 or 60 years old, were invited to the screening study. Traditional risk factors were obtained and a non-contrast CT-scan was performed to assess the CAC score. Results A total of 1211 individuals participated, of whom 54 (4%) had T2D while 1157 (96%) were without diabetes. CAC was present in 62% of the patients with T2D versus 44% in those without (p=0.013). Also the prevalence of traditionally risk factors was high in patients with T2D as compared to subjects without T2D. When adjusting for age, gender, smoking, hypertension and hypercholesterolemia in multivariate logistic regression, T2D was not associated with presence of CAC (OR=1.0; 95% confidence interval 0.5 - 2.0, p=0.94). Conclusions One-third of patients with T2D did not have any CAC, and T2D per se was not associated to CAC.
Keywords: Type 2 Diabetes Mellitus; atherosclerosis; coronary artery disease; risk assessment; cohort studies.